Long-term Conservative Follow-up in Children with High-grade Vesicoureteral Reflux and an Abnormal Dimercaptosuccinic Acid Scan - Pankaj V Deshpande (Pediatric Infectious Disease)
Aim: High-grade vesicoureteral reflux (VUR) with an abnormal dimercaptosuccinic acid (DMSA) scan is considered to be a high risk for recurrent urine infections (UTIs) and advised surgery in most parts of India to prevent the high risk of UTIs and renal damage. In this retrospective study, we looked at 82 children with high-grade VUR and abnormal DMSA, having conservative follow-ups, to determine if they had recurrent UTIs and what their renal function and growth were at the end of follow-ups. Materials and methods: Records of 82 children who were being followed up conservatively for high-grade VUR and an abnormal DMSA were seen for the number of UTIs, present kidney function and urine protein/creatinine ratio, and growth at follow-up, reason for micturating cystourethrogram (MCUG) and if circumcision had been done. The follow-up period was 3–19 years. Results: Only two children had developed UTIs amongst the 82 after stopping prophylaxis. All the children had normal growth, kidney function, blood pressure, and urine protein/creatinine ratio at follow-up. A total of 59 children (39 boys and 20 girls) (72%) had MCUG done after UTI while 20 (19 boys and one girl) (24%) children had it done for antenatal hydronephrosis (four of whom had developed UTI immediately after MCUG but had remained free of UTIs thereafter). Conclusion: Conservative management of high-grade VUR, either unilateral or bilateral, in children with an abnormal DMSA does not lead to recurrent severe UTIs. Prophylaxis can be stopped after a period of 6 months to 1 year, even in high-grade VUR. Repeated MCUG or DMSA scans seem unnecessary. Almost all boys remained well with no UTI without circumcision. All children have normal growth, kidney function, urine protein/creatinine ratio, and blood pressure at present. (15 years follow-up in 17 children). Clinical significance: Conservative follow-up in high-grade VUR with abnormal DMSA is not associated with recurrent UTIs in all patients and does not affect renal function or growth adversely.